2022
DOI: 10.1029/2022gl097870
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of Magnetotail Current Sheet Prior to Magnetic Reconnection Onset

Abstract: The magnetotail current sheet configuration determines magnetic reconnection properties that control the substorm onset, one of the most energetic phenomena in the Earth’s magnetosphere. The quiet‐time current sheet is often approximated as a two‐dimensional (2D) magnetic field configuration balanced by isotropic plasma pressure gradients. However, reconnection onset is preceded by the current sheet thinning and the formation of a nearly one‐dimensional (1D) magnetic field configuration. In this study, using p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Our observations show that TCSs typically have a strong current density up to 10 nA/m 2 , which would lead to the formation of a very strong magnetic tension force. However, it is unlikely that the plasma pressure gradient is strong enough to balance this force, and it is suggested that the key contribution of ion nongyrotropy ( P xz ) should be considered (An et al., 2022; Arnold & Sitnov, 2023; Artemyev et al., 2021; Artemyev, Angelopoulos, & Runov, 2016; Runov et al., 2021; Sitnov & Arnold, 2022). This nongyrotropy is expected to be contributed by hot ion population, likely outside the FPI energy range (see discussion in Arnold & Sitnov, 2023; Artemyev et al., 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Our observations show that TCSs typically have a strong current density up to 10 nA/m 2 , which would lead to the formation of a very strong magnetic tension force. However, it is unlikely that the plasma pressure gradient is strong enough to balance this force, and it is suggested that the key contribution of ion nongyrotropy ( P xz ) should be considered (An et al., 2022; Arnold & Sitnov, 2023; Artemyev et al., 2021; Artemyev, Angelopoulos, & Runov, 2016; Runov et al., 2021; Sitnov & Arnold, 2022). This nongyrotropy is expected to be contributed by hot ion population, likely outside the FPI energy range (see discussion in Arnold & Sitnov, 2023; Artemyev et al., 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, magnetotail models struggle to incorporate such a strong pressure gradient simultaneously across a wide radial range (see discussion in Sitnov, Stephens, et al., 2019; Sitnov et al., 2021). Thus, thin CSs either should form locally, within a radially confined region of strong pressure gradient (Birn et al., 2004; Liu et al., 2014; Schindler & Birn, 2002), or should be balanced by alternative mechanisms that do not involve strong pressure gradients (see discussion in Artemyev et al., 2021; An et al., 2022; Arnold & Sitnov, 2023). Further statistical investigations of the middle and distant magnetotail CSs should shed light on how often thin CSs typically form at these distances.…”
Section: Introductionmentioning
confidence: 99%
“…(b) To what extent are these characteristics influenced by solar wind conditions? The answer to the first question should provide important data for new CS models (see discussion in Sitnov & Arnold, 2022;Arnold & Sitnov, 2023;An et al, 2022An et al, , 2023). The answer to the second question should reveal if the solar wind is the main driver of thin CS formation in the middle tail.…”
Section: Introductionmentioning
confidence: 99%
“…Instabilities of such current sheets, either internally or externally driven, can result in the magnetic reconnection, a key process during magnetospheric substorms (Sitnov et al., 2019). The current sheet configuration directly controls the magnetic reconnection onset (e.g., An et al., 2022; Y.‐H. Liu et al., 2014; Lu et al., 2020; Sitnov et al., 2021), which further transforms the magnetic energy to the plasma heating and charged particle acceleration (e.g., Birn et al., 2012; Gonzalez & Parker, 2016).…”
Section: Introductionmentioning
confidence: 99%